2022
DOI: 10.3389/fphar.2022.850053
|View full text |Cite
|
Sign up to set email alerts
|

Cariporide Attenuates Doxorubicin-Induced Cardiotoxicity in Rats by Inhibiting Oxidative Stress, Inflammation and Apoptosis Partly Through Regulation of Akt/GSK-3β and Sirt1 Signaling Pathway

Abstract: Background: Doxorubicin (DOX) is a potent chemotherapeutic agent with limited usage due to its cumulative cardiotoxicity. The Na+/H+ exchanger isoform 1 (NHE1) is a known regulator of oxidative stress, inflammation, and apoptosis. The present study was designed to investigate the possible protective effect of cariporide (CAR), a selective inhibitor of NHE1, against DOX-induced cardiotoxicity in rats.Methods: Male Sprague-Dawley rats were intraperitoneally injected with DOX to induce cardiac toxicity and CAR wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 54 publications
1
11
0
Order By: Relevance
“…Translocation of Bax from the cytoplasm to the mitochondria promotes the release of cytochrome c from the mitochondria to activate caspase3, whereas Bcl-2 prevents the release of cytochrome c from the mitochondria and thus inhibits the process of apoptosis. 30 In our study, we also found that CA treatment significantly ameliorated DOX-induced apoptosis in cardiomyocytes and cardiac tissues, as indicated by the decreased activation of Bax, along with restored Bcl-2 expression levels. Indeed, activating Nrf2 via CA could decrease DOX-induced cardiomyocyte apoptosis and the inhibition of Nrf2 abolished this protective effect provided by CA.…”
Section: Discussionsupporting
confidence: 74%
“…Translocation of Bax from the cytoplasm to the mitochondria promotes the release of cytochrome c from the mitochondria to activate caspase3, whereas Bcl-2 prevents the release of cytochrome c from the mitochondria and thus inhibits the process of apoptosis. 30 In our study, we also found that CA treatment significantly ameliorated DOX-induced apoptosis in cardiomyocytes and cardiac tissues, as indicated by the decreased activation of Bax, along with restored Bcl-2 expression levels. Indeed, activating Nrf2 via CA could decrease DOX-induced cardiomyocyte apoptosis and the inhibition of Nrf2 abolished this protective effect provided by CA.…”
Section: Discussionsupporting
confidence: 74%
“…Pyroptosis mainly occurs via the canonical caspase-1-dependent pathway, and we examined whether Dox caused pyroptosis in rat cardiomyocytes through the activation of caspase-1. GSK-3β, has been proved to play a role in Dox induced cardiotoxicity (20,21). Our results showed that after Dox administration, the proportion of p-GSK-3β positive heart slices decreased (Figures 2A, B) and cleaved-caspase-1 increased (Figures 2A, C).…”
Section: Ticagrelor Inhibits Gsk-3β-mediated Pyroptosis In Rats Treat...mentioning
confidence: 61%
“…Our recent study revealed that GSK-3β regulate pyroptosis (19). GSK-3β contributes to Dox-induced cardiotoxicity by mediating oxidative stress, inflammation and apoptosis (20). Therefore, we want to determine whether GSK-3β mediated pyroptosis is the key to DOX induced cardiotoxicity.…”
Section: Introductionmentioning
confidence: 99%
“…Other review studies also show that the mechanism of cardiotoxicity caused by other drugs is still unclear. However, various reasons such as oxidative stress, apoptosis, and inflammation can aggravate this condition (31)(32)(33)(34).…”
Section: Discussionmentioning
confidence: 99%